Get into the Grave: Notions of Community Social Identity in a Late 3rd Millennium Site, Derived from an Experimental Carving of a Shaft Tomb at Ramat Bet Shemesh (Israel) - Yoav Tsur; Nofar Kahalani; Yithzak Paz; Roi Nickelberg (EXARC Journal)
Khirbet el-Alia is a large mound, located north-east of Tel Yarmouth, in the Ramat Bet Shemesh region of Israel. An excavation that was conducted north of the mound revealed the remains of a settlement and an adjacent cemetery of shaft graves, dating back to the Intermediate Bronze Age (IBA). The excavation yielded important notions on the material culture as well as on symbolic realms, group identity and social differentiation of the settlers in this site. One of the main characteristics that reflected these issues was the variety in the efforts and resources invested in carving the shaft tombs. In order to investigate this phenomenon of conspicuous consumption of human labour and to understand and explain its social implications on late third millennium society, we used experimental archaeology, thus we carved our own shaft grave, documented the work in progress and interpreted its results and the socio-economic implications on this ancient society.